Generosity the Second Time Around: Determinants of Individuals’ Repeat Donation Intention - Beldad, Ardion; Snip, Babiche; van Hoof, Joris (Nonprofit and voluntary sector quarterly, 2014)
Studies into the factors influencing first-time monetary donation intention abound. However, the determinants of repeat donation intention have not yet received significant attention within the academic community. For this study, a survey was implemented with residents of two cities in the eastern part of the Netherlands to determine the factors influencing their repeat donation intention. The study shows that respondents’ intention to continue donating to a charitable organization is predicated on their positive experience with that organization. Furthermore, this repeat donation is also influenced by respondents’ affinity with the cause of the charitable organization, their trust in the organization, and the organization’s positive reputation. The perceived risk of donating negatively influences repeat donation intention. It is surprising, however, that a sense of moral obligation to help others does not impact respondents’ intention to continue donating.